Cancer Registration and Its Role in Cancer Epidemiology and Cancer Control - BRAY, FREDDIE (Indonesian Journal of Cancer, 2010)
UICC World Cancer Declaration-secondtarget for 2020â¢The measurement of the global cancer burden and the impact of cancer control interventions will have improved significantlyâ¢WHO 2008-2013 Action PlanGlobal Strategy for the Prevention and Control of Non-communicable Diseasesâ¢Objective 6: To monitor non-communicable diseases and theirdeterminants and evaluate progress at the national, regional andglobal levelhttp://indonesianjournalofcancer.or.id/e-journal/index.php/ijoc/article/view/131